Curriculum Development of Early Childhood Education through Society Empowerment as Potential Transformation of Local Wisdom in Learning - Prasetyo, Agung; Kristanto, Kristanto (Indonesian Journal of Early Childhood Education Studies, 2015)
The goal of this research is to identify potential transformation of local wisdom that can support the execution of early childhood education learning in Central Java Indonesia and examine community empowerment program in developing the curriculum of early childhood education. This research is in the form of research and development.The outcome of this research is the design of curriculum development of early childhood education that can give real examples for the educators in empowering community’s role as a form of potential transformation of local wisdom in early childhood education learning such as 1) Potential transformations of local wisdom which can support the execution of early childhood education learning in Central Java Indonesia. The steps are a) Choosing themes and sub-themes based on the local potential; b) identifying playing activities c ) composing a daily plan. 2) Involving parents in community empowerment program in developing the curriculum of early childhood education.How to citePrasetyo, A., & Kristanto, K. (2015). Curriculum Development of Early Childhood Education through Society Empowerment as Potential Transformation of Local Wisdom in Learning. Indonesian Journal Of Early Childhood Education Studies, 4(1), 30-34. doi:10.15294/ijeces.v4i1.9450